2021
DOI: 10.1186/s12943-021-01352-4
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-derived exosomal miR-15a-5p as a promising diagnostic biomarker for early detection of endometrial carcinoma

Abstract: Endometrial cancer (EC) is a major cause of death among gynecologic malignancies. To improve early detection of EC in patients, we carried out a large plasma-derived exosomal microRNA (miRNA) studies for diagnostic biomarker discovery in EC. Small RNA sequencing was performed to identify candidate exosomal miRNAs as diagnostic biomarkers in 56 plasma samples from healthy subjects and EC patients. These miRNA candidates were further validated in 202 independent plasma samples by droplet digital PCR (ddPCR), 32 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(70 citation statements)
references
References 15 publications
2
57
0
Order By: Relevance
“…Kong et al noticed that high expression of miR-15a-5p led to the promotion of cell proliferation and invasion in glioblastoma [ 25 ], which was also confirmed in ovarian cancer [ 26 ]. Interestingly, the studies conducted so far indicate that the level of miR-15a-5p was reduced both in the serum of patients [ 27 ] and in endometrial cancer cells and tissues [ 28 ]. Our results, therefore, may suggest that the interaction of this miRNA with DRD5 may play a role in the progression of endometrial cancer by regulating its proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Kong et al noticed that high expression of miR-15a-5p led to the promotion of cell proliferation and invasion in glioblastoma [ 25 ], which was also confirmed in ovarian cancer [ 26 ]. Interestingly, the studies conducted so far indicate that the level of miR-15a-5p was reduced both in the serum of patients [ 27 ] and in endometrial cancer cells and tissues [ 28 ]. Our results, therefore, may suggest that the interaction of this miRNA with DRD5 may play a role in the progression of endometrial cancer by regulating its proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, mutant EGFRvIII mRNA was detected in serum exosomes of glioblastoma patients [ 39 ]. Zhou et al reported that the expression level of exosomal miR-15a-5p was 7-19 times higher in endometrial cancer than that in other cancer types [ 40 ]. Additionally, high expression of exosomal miR-1247-3p was positively associated with lung metastasis from liver cancer, which indicated a poor outcome [ 41 ].…”
Section: Exosome Biogenesis and Contentsmentioning
confidence: 99%
“…Interestingly, several studies have identified miRNAs in extracellular vesicles from different body fluids, e.g., urine [ 124 ], peritoneal lavage [ 125 ], and blood serum [ 126 ]. Recently, a large plasma-derived exosomal miRNA study identified miR-15a-5p as a valuable diagnostic biomarker for the early detection of EC [ 127 ]. Another study identified four miRNAs associated with EC (oncogenic miRNAs miR-135b and miR-205, as well as tumor suppressor miRNAs miR-30a-3p and miR-21) [ 123 ].…”
Section: Endometrial Precancerous Lesions and Early-stage Endometrial Cancermentioning
confidence: 99%
“…Therefore, a two-step strategy, using both CA-125 and TVS, has been developed. Several studies have used a two-phase strategy to detect early-stage ovarian tumors and have confirmed its good specificity and positive predictive value in a population of women at a moderate risk of ovarian cancer [ 3 , 127 , 128 ].…”
Section: Strategies For the Early Detection Of Epithelial Ovarian Cancer (Eoc)mentioning
confidence: 99%